Democracy at Stake: Self-Censorship as a Self-Defence Strategy for Journalists - Gerald Walulya; Goretti L. Nassanga (Media and Communication, 2020)
The media play an essential role of informing and mobilising voters as well as facilitating a two-way communication process between citizens and those vying for electoral offices during elections. This allows citizens to get information on various issues from the contenders, which largely informs their electoral decisions. In most less democratic societies however, this media function is increasingly becoming difficult to fulfil due to challenges journalists encounter during electoral processes. Using Uganda’s last general elections in 2016 as a case study, this article discusses the safety of journalists during elections basing on findings from a bigger study on the media coverage of the 2016 elections, supplemented by in-depth interviews with 10 journalists who covered the elections. In addition, the analysis makes reference to the 2016 Uganda Press Freedom Index. Findings of this research show that journalists face more safety and security risks during elections particularly perpetuated by state security agencies. Compared to previous elections, the 2016 elections also recorded the highest number of victims who were female journalists. This article highlights key challenges journalists face during elections, which include: state harassment and intimidation, arrest of those considered critical to the state, and denial of access to important information. Due to concerns of their own safety, journalists have responded to the insecure work environment by engaging in self-censorship, thereby giving biased or limited information to the public. The article identifies gaps that media development agencies can help to close if the media are to play their rightful role in a democratic society, especially during the electoral process.